Nobody Wants to Read Anymore! Using a Multimodal Approach to Make Literature Engaging - Riki Thompson; Matthew McIlna (CLELEjournal, 2019)
Reports about apparent declines in reading continue to gain attention, playing into social anxieties about literacy and the state of education. In this article, we examine concerns about changing reading habits, address the role of digital media in literacy practices, and the problem of adequate access to reading materials. To meet the rapidly changing literacy demands of today's students, addressing motivation, teaching visual literacy, and instilling a lifelong love of reading are increasingly important. We argue for integration of non-traditional texts and application of multimodal reading approaches to motivate students, reinvigorate curricula, and meet continually evolving education standards. Our approach calls for integrating a wide range of texts, including comics, graphic novels, and film, for language learning and into the literary curriculum. In English language teaching (ELT) contexts, the use of visual texts has been shown to have positive outcomes, including increasing student participation, improving reading comprehension, inspiring students' motivation and building confidence.